High carrier mobility and remarkable photovoltaic performance of two-dimensional Ruddlesden-Popper organic-inorganic metal halides (PA)₂(MA)₂M₃I₁₀ for perovskite solar cell applications - Sun, Ping-Ping (2022)
Two-dimensional Ruddlesden–Popper (2DRP) metal halides have attracted extensive attention in photovoltaic applications due to their high stability, low self-doping levels and long-lived free carriers. Among them, (PA)2(MA)2Pb3I10 presents itself as a superior candidate, demonstrating greater moisture resistance and improved heat and light stability over many other 2DRP metal halides. This study takes on the opportunity to search for lead-free alternatives by investigating the optoelectronic and carrier transport properties, as well as the photovoltaic performance of such (PA)2(MA)2M3I10 type metal halides as the photovoltaic absorber, where M = Pb, Cd, Cr, Cu, Ge, Mn, Ni, Sn, Yb, Zn. Our results indicate that the bandgap of (PA)2(MA)2M3I10 can be tuned to the optimum photovoltaic application range of 0.9–1.6 eV, along with improved optical and enhanced photo-response capacity, when Sn, Cd, Mn, Ge, and Zn are used to replace Pb. In particular, (PA)2(MA)2Zn3I10 possesses the largest Stokes shift and Huang-Rhys factor, while showing the best photoluminescence tendency and broadest emission nature. (PA)2(MA)2Ge3I10 displays the most excellent of carrier transport capacities with high mobilities of 73 cm2 V−1 s−1 and 43 cm2 V−1 s−1 for electron and hole carriers, respectively, which are even comparable to that of 3D counterparts. Furthermore, (PA)2(MA)2Zn3I10 is predicted to have the highest power conversion efficiency of 23.36% based on an empirical energy loss (0.5 eV), which is quite close to the Shockley–Queisser limit, thereby featuring it as a suitable absorber for photovoltaic applications. These findings shed light on new strategies for designing and developing lead-free 2DRP metal halides targeted at future applications in photovoltaic solar cell devices.